Expression, subcellular localisation, and possible roles of dipeptidyl peptidase 9 (DPP9) in murine macrophages. (2nd March 2017) - Zapletal, Emilija; Cupic, Barbara; Gabrilovac, Jelka
Abstract : Dipeptidyl peptidase 9 (DPP9) is a peptidase of the DPPIV gene family, and its role in immune responses has been reported. In this study, we compared the messenger RNA expression profile of DPP9 to that of the related DPP8 and DPPIV in murine haematopoietic and lymphatic tissues. A similar order of expression levels was observed for all 3 peptidases: peritoneal macrophages < bone marrow < spleen ≤ lymph nodes. Also, we examined the subcellular localisation of DPP9 and its possible role(s) in J774 cell line of macrophage origin. DPP9 was dominantly expressed intracellularly. DPPIV‐like enzymatic activity was mostly present in cytoplasm, but also in cell membranes and organelles/vesicles. Decreased expression of DPP9 was observed upon activation of J774 cells by combined treatment with interferon gamma and lipopolysaccharide. Changes induced by DPP9 gene silencing in J774 cells suggest possible role of DPP9 in regulation of proliferation and activation status. The colocalisation of DPP9 with endocytosed DQ‐OVA demonstrated in endosomes of J774 cells might suggest the role of DPP9 in peptide processing within endosomal/vesicular compartment.